Effect of green tea (Camellia sinensis L.) extract on the quality of Gaok rooster spermatozoa stored in a fructose-egg yolk-milk diluent at room temperature - Raffael Darrel Juliano; Nove Hidajati; Sri Hidanah; Tatik Hernawati; Tita Damayanti Lestari; Pudji Srianto (Universitas Airlangga, 2026)
This study evaluated the effect of a fructose-egg yolk-milk diluent supplemented with different concentration of green tea leaf extract (Camellia sinensis L.) on the quality of rooster semen stored at room temperature (25 °C). Semen was collected from five healthy Gaok roosters (1.5-2 years old), pooled and allocated into four treatment groups: T0 (diluent only, control), T1 (diluent + 0.005 mg green tea extract/10 mL), T2 (diluent + 0.010 mg/10 mL), and T3 (diluent + 0.015 mg/10 mL). Semen quality was evaluated over a 6-hour storage period, focusing on progressive motility, viability, plasma membrane integrity (assessed using the hypoosmotic swelling test), and morphological abnormalities. The addition of green tea extract significantly improved progressive motility, sperm viability, and membrane integrity compared to the control throughout the storage period (p <0.05). These improvements followed a dose–response trend, with the intermediate dose (T2, 0.010 mg/10 mL) showing the most stable and sustained protective effects. No significant differences were observed in spermatozoa morphological abnormalities among treatments (p >0.05), with values remaining low and comparable across all groups. Overall, the results suggest that incorporating green tea leaf extract into a fructose-egg yolk-milk diluent can enhance the short-term preservation of rooster semen by maintaining motility, viability, and membrane functionality at 25 °C, without adversely affecting morphology. The optimal dose identified in this study was 0.010 mg per 10 mL diluent (T2), which provided effective protection for up to 6 hours of storage. In conclusion, green tea extract shows promise as a practical antioxidant additive for improving the short-term handling and transport of rooster semen under field conditions.